Staphylococcus haemolyticus: An emerging threat in cancer patient (Indian Journal of Case Reports, 2020)
Staphylococcus haemolyticus, a coagulase-negative Staphylococcus, is an opportunistic bacterial pathogen that colonizes human skin and is known for its high antibiotic resistance. After Staphylococcus epidermidis, the second most frequently isolated coagulase-negative Staphylococcus is S. haemolyticus. Increasing clinical significance of S. haemolyticus could be due to the great adaptability and the ability of the organism to survive in the hospital environment, especially on indwelling catheters, and the ability to acquire multidrug resistance against available antimicrobial agents. We report a case of a 40-year-old female diagnosed with mixed-lineage leukemia-positive pre-B acute lymphoblastic leukemia. The patient had undergone myeloablative T-replete haploidentical allogeneic stem cell transplantation. Later on, she developed skin graft versus host disease on day 83 and S. haemolyticus was isolated from the skin cultures. The patient was successfully managed with injection teicoplanin and skin care, but subsequently, she succumbed to multidrug-resistant Klebsiella pneumoniae infection.